A novel cable-driven antagonistic joint designed with variable stiffness mechanisms. (May 2022) - Li, Zhongyi; Chen, Weihai; Zhang, Jianbin; Li, Qihang; Wang, Jianhua; Fang, Zaojun; Yang, Guilin
Abstract: In this paper, a novel cable-driven antagonistic joint of variable stiffness is presented. The joint features antagonistic, series-elastic actuation with novel variable stiffness mechanisms (VSMs). The VSM is able to achieve adjustable quadratic torque–deflection characteristics through an easy offline adjustment of its design parameters. This makes it possible for us to simultaneously and independently control both joint position and stiffness in different manners, which increases the adaptability of the system to application variability and change. In the paper, mechanics models are developed for both antagonistic joint and VSM, with which an optimization method is used to optimize the VSM to produce desired quadratic behaviors. The models and optimization method are first validated by simulations and then demonstrated experimentally with a prototype. The proposed joint is finally applied in a wearable exoskeleton. Highlights: A novel cable-driven antagonistic joint designed with variable stiffness mechanisms (VSMs) is proposed. The angle and stiffness of the new joint can be controlled independently. Mathematical models for both the antagonistic joint and the VSM are developed. Optimization of the VSM design is conducted to achieve specifiable quadratic behaviors. The models are demonstrated experimentally with an optimized prototype.